Hyperprolactinemia after menopause: Diagnosis and management. (September 2021) - Auriemma, Renata S.; Pirchio, Rosa; Pivonello, Rosario; Colao, Annamaria
Highlights: Most prolactinomas are diagnosed in women of reproductive age and are generally microadenomas. Prolactinomas diagnosed in postmenopausal women are less common and usually not associated to the typical syndrome induced by prolactin excess, including infertility and oligo-amenorrhea. The diagnosis of prolactinomas after menopause generally results in a clinically relevant delay. Data on the management and prognosis of prolactinomas in postmenopausal women are scant and prospective studies are completely lacking. The physiologic decline of prolactin levels during menopause and the lack of a clinical syndrome characterized by fertility concerns impose the need for a careful reassessment of therapeutic management in such patients. Postmenopausal women with microprolactinomas may be successfully withdrawn from medical therapy with dopamine agonists, whereas those with macroprolactinomas should be maintained on dopamine agonists to prevent potential, although rare, tumor enlargement. Abstract: Most prolactinomas are diagnosed in women of reproductive age and are generally microadenomas. Prolactinomas diagnosed in postmenopausal women are less common and are not usually associated with the typical syndrome induced by prolactin excess, including infertility and oligo-amenorrhea. This implies that the diagnosis of prolactinomas after menopause may be delayed and require greater clinical effort. Limited data are available on the management and prognosis of prolactinomas in postmenopausal women. However, the physiologic decline of prolactin levels during menopause and the lack of fertility concerns, which represent specific indications for medical treatment with dopamine agonists, might require a careful reassessment of therapeutic management in such patients. Postmenopausal women with microprolactinoma may be successfully withdrawn from medical therapy with dopamine agonists, whereas in those with macroprolactinomas greater caution is advisable before dopamine agonists are discontinued, considering the potential, although rare, tumor enlargement. This review focuses on the diagnostic challenges and therapeutic management of prolactinomas in postmenopausal women.